Microeconometrics with R - Croissant, Yves 1969- (Chapman & Hall/CRC the R series, 2025)
"This book is about doing microeconometrics, defined by Cameron and Trivedi (2005) as the analysis of individual-level data on the economic behavior of individuals or firms using regression methods applied to cross-section and panel data with R. Microeconometrics became increasingly popular in the last decades, thanks to the availability of many individual data sets and to the development of computer performance. R appeared in the late nineties as a clone of S. It became increasingly popular among statisticians, especially in fields where S was widely used. 20 years ago, using R for doing econometrics analysis required a lot of programming because a lot of core methods of econometrics were not available in R. Nowadays, most of the basic methods described in the book are available in contributed packages. Moreover, the set of packages called the tidyverse developed by Rstudio (now Posit) for all the basic tasks of an applied statistician (importing, tidying, transforming and visualizing data set) makes the use of R faster and easier. The book uses extensively specialized econometrics packages and the tidyverse and seeks to demonstrate that the adoption of R as the primary software for an econometrician is a relevant choice. The first part of the book is devoted to the ordinary least square estimator. Matrix algebra is progressively introduced in this part and a special attention is paid on the interpretation of the estimated coefficients. The second part goes beyond the basic OLS estimator by testing the hypothesis on which this estimator is based on and providing more complex estimators relevant when some of these hypotheses are violated. Finally, the third part of the book presents specific estimators devoted to special responses, eg count, binomial or duration data"--